Dynamics of pesticide residues in cardamom growing soils of Iddukki district. - Nath Siji N (Department of Soil Science and Agricultural Chemistry,College of Agriculture, 2011)
The pesticide use pattern in cardamom growing tracts of Idukki district shows that the farmers are applying plant protection chemicals aggressively and the liberal and continual use of pesticides has disturbing consequences on the ecosystem. The decision regarding the type of chemicals to be used, dosage, frequency of application are fixed by the farmers themselves or as per the directions of company representatives and they are not following the recommendation of KAU or Spices Board. The improper usage of these chemicals resulted in pollution of the cardamom ecosystem especially the soil and water with toxic xenobiotics. Hence in order to assess the residue level and to study the extend of pollution due to pesticides, soil and water samples were collected from the cardamom growing plantations of Idukki district. In multi residue method validation, soil samples were spiked at five different levels (0.01 µg g-1, 0.05 µg g-1, 0.1 µg g-1, 0.5 µg g-1, 1 µg g-1) and extraction was carried out using various solvent/ solvent system and the method which gave 70-110 per cent recovery with RSD <20 per cent was selected. The same procedure was adopted for further estimation of residues from soil samples. The pesticide hot spots, were selected mainly in three locations, Kattappana, Pampadumpara and Nedumkandam Panchayath in Idukki district and five farmers were identified randomly from each location. Soil and water samples were collected before and after spraying of insecticides for a period of six months starting from December to May at two different depth at 0-15 cm and 15-30 cm depth from the selected plantations. In the monitoring study, samples collected at 0-15 cm depth were found to contain higher level of pesticide residues. The samples were frequently detected with residues of organophosphorus insecticides like phorate, chlorpyriphos, quinalphos, profenophos, methyl parathion and relatively lower number of samples were found to contain residues of endosulphan and synthetic pyrethroids. The samples collected from the lower depth 15-30 cm were contaminated with residues at a lower level. The physico chemical properties of the soil were analysed and it was found that the soils were rich in organic matter content (3.63-3.74%), acidic to near neutral pH (5.72-6.04) and have higher fertility status. The higher organic matter content of the soil favours higher rate of adsorption of the insecticide. Water samples were collected from the selected locations and analysed for the presence of pesticide residues and it was found that none of the samples were contaminated with pesticide residues. A field dissipation study was carried out with the neonicotinoid group of insecticide, imidacloprid applied at three different levels (0.05 ml l-1, 0.10 ml l-1, 0.20 ml l-1) in cropped and non-cropped condition. The half life of the chemical calculated under both the situation. The highest half life (4.25 days) was obtained when imidacloprid applied in non- cropped situation at double the recommended dose (0.20 ml l-1) and the lowest half life (2.55 days) was obtained in cropped situation when the insecticide was applied at the lowest dose (0.05 ml l-1). The half life value obtained in cropped condition was lower compared to the non cropped situation. The faster degradation of the chemical under the cropped situation may be due to the higher activity of soil microorganisms and rhizosphere effect in addition to other soil factors like pH and organic carbon content.